2009
DOI: 10.1111/j.1464-410x.2008.08123.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bladder cancer recurrence rate with cardioprotective aspirin after intravesical bacille Calmette‐Guérin

Abstract: PATIENTS AND METHODSIn all, 43 patients with carcinoma in situ (CIS) and/or high-grade papillary bladder cancer were treated with intravesical BCG. Patients were stratified according to whether they took cardioprotective aspirin after treatment, and Kaplan-Meier curves of RFS were compared by log-rank analysis. Multivariable analysis was used for potentially confounding factors, including maintenance BCG, the presence of CIS, and smoking status. RESULTSOf patients taking cardioprotective aspirin, the 5-year RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 14 publications
(17 reference statements)
0
28
1
Order By: Relevance
“…Aspirin, along with warfarin and clopidogrel, belongs to a class known as fibrin clot inhibitors, which may theoretically interfere with the fibrin-mediated uptake of BCG, thereby rendering it less efficacious [16,18]. In a study on 43 patients with NMIBC treated with intravesical BCG, however, Gee et al [17] reported a significantly higher recurrence-free survival in patients taking cardioprotective aspirin compared to those not on aspirin on multivariable analysis (HR 0.179, p = 0.001), while no effect was seen on progression-free survival. This is contrary to the postulated inhibitory effect of aspirin on BCG uptake.…”
Section: Aspirin Nsaids and Cox Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin, along with warfarin and clopidogrel, belongs to a class known as fibrin clot inhibitors, which may theoretically interfere with the fibrin-mediated uptake of BCG, thereby rendering it less efficacious [16,18]. In a study on 43 patients with NMIBC treated with intravesical BCG, however, Gee et al [17] reported a significantly higher recurrence-free survival in patients taking cardioprotective aspirin compared to those not on aspirin on multivariable analysis (HR 0.179, p = 0.001), while no effect was seen on progression-free survival. This is contrary to the postulated inhibitory effect of aspirin on BCG uptake.…”
Section: Aspirin Nsaids and Cox Inhibitorsmentioning
confidence: 99%
“…Aside from their cholesterol-lower mechanism via inhibition of 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase, statins have also independently demonstrated immunomodulatory properties by inhibiting T H 1-cell activation and development while promoting anti-inflammatory T H 2 cytokine secretion [14,15]. Concomitant use of anti-inflammatory agents or fibrin clot inhibitors with intravesical BCG has generated conflicting reports regarding the resultant efficacy of BCG in treating NMIBC, owing to the hypothesized interference with BCG's fibronectin-mediated uptake [16][17][18] and subsequent immunomodulatory effects [19][20][21][22][23]. In the present study, we sought to evaluate whether the use of anti-inflammatory agents affects oncologic outcomes in patients receiving intravesical BCG therapy for high-grade (HG) NMIBC.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize the best available evidence, we selected 12 studies that met the inclusion criteria for this review article of which five studies were published prior to 2011. The associations of smoking with disease recurrence and progression, the two most important disease outcomes in NMIBC, are summarized in Table 1 [11][12][13][14][15][16][17][18][19][20][21][22]. Although there are minor variations in disease outcome definitions among studies, the definitions were sufficiently similar to allow for evidence synthesis.…”
Section: Impact Of Smoking On Outcomesmentioning
confidence: 99%
“…The majority of studies (10 of 12) investigated the associations of smoking status with disease recurrence [11][12][13][14][15][16]17 19,20]. Attributable to variations in the study sample sizes, there were variations of the comparator groupings.…”
Section: Impact Of Smoking On Outcomesmentioning
confidence: 99%
“…Although these drugs have a potential negative effect on the immune response to BCG treatment, neither had an effect on the clinical efficacy of BCG therapy in multiple clinical studies. [27][28][29][30][31][32] Other relative contraindications are prosthetic valves or orthopaedic hardware. However, a large phase II study with BCG combination therapy reported no infectious complications in the absence of prophylactic anti biotics, suggesting this population represents a lowrisk setting.…”
Section: Practical Issues Of Bcg Administrationmentioning
confidence: 99%